Proposed Framework for the Role of Personality Traits in the Relationship between Listener‘s Participation & Perceived Value of the Service of Radio and its Reflection on the Satisfaction - Mohammed, Naglaa; Rajab, Jehan; Ahmed, Hanan (The Arab Journal of Administration, 2023)
The aim of the study: To verify the nature of the relationship between customer participation and their perceived value in light of the influence of personality styles as a modified variable on the relationship between them. Study methodology: The research design is based on the inferential descriptive approach that is based on combining theoretical study and field study Data and study sample: The primary data was collected through a questionnaire for a sample of 384 individuals, and the researchers resorted to the interceptor sample method as one of the probability sampling methods through one single interception on a regular basis approximately every twenty minutes, so that the data were collected during all days of the week and at all Working hours during the day, at all entrances and exits of shopping centers in Greater Cairo, without prior agreement with any of the participants. Results of the study: There is a positive statistically significant effect of the listener’s participation on the perceived value of the broadcasting service, in part with regard to the effect of listening carefully to the radio on the perceived value of the broadcasting service in its three dimensions (the value of ease, emotional value, and cognitive value), and its rejection in relation to the effect of participating in programs. Broadcasting on the three dimensions of the perceived value of the broadcasting service. It was also found that there is a statistically significant effect of personality patterns on the relationship between the participation of the listener and the perceived value of the broadcasting service. Except that. Conclusion: The study recommends setting a radio business strategy targeting multiple formats that allow listeners to participate in radio programs, taking into account their different personality styles, and conducting more research on personality styles in this field.